A bibliometric analysis of translation criticism studies and its implications. (2nd September 2020) - Huang, Qin; Xin, Xiaoxiao
ABSTRACT: This paper presents an overview of translation criticism (TC) based on a bibliometric analysis of data in the online Bibliography in Interpreting and Translation (BITRA). The analysis focuses on, among other issues, the evolution of research output, publication types, authors and themes. Results suggest that TC research experienced an overall trend of growth from the 1940s to the 2010s, mainly in the form of journal articles and book chapters. It has attracted greater attention from young scholars during the past two decades. Meanwhile, publications, spearheaded by researchers with continuing interests in this field and some very active and productive journals, have a wide distribution of publication outlets and authors. Additionally, this research identifies some popular topics, such as quality assessment models and methods, reviews, evaluations, text-based linguistic analysis, poetry and novels. Also, it reveals that in the database, case studies are widely applied, and scholars' attention has gradually shifted from linguistic to extra-linguistic factors. Overall, the field is still relatively underresearched in the translation studies (TS) community with some potentially underexplored areas. Thus implications for future research, such as strengthening collaboration, intensifying research in online reviewing/criticism, enhancing corpus-based research, and research from cultural and sociological perspectives, are proposed.